(3x-4)=(7x-54)

Simple and best practice solution for (3x-4)=(7x-54) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x-4)=(7x-54) equation:



(3x-4)=(7x-54)
We move all terms to the left:
(3x-4)-((7x-54))=0
We get rid of parentheses
3x-((7x-54))-4=0
We calculate terms in parentheses: -((7x-54)), so:
(7x-54)
We get rid of parentheses
7x-54
Back to the equation:
-(7x-54)
We get rid of parentheses
3x-7x+54-4=0
We add all the numbers together, and all the variables
-4x+50=0
We move all terms containing x to the left, all other terms to the right
-4x=-50
x=-50/-4
x=12+1/2

See similar equations:

| 12h=540 | | 28=–2m | | 3u(u-1)(u-2)=0 | | p-50=-10 | | 20x9=10x9 | | 81=81-7t | | 10.x=80 | | Y=3x= | | z-306=143 | | 15c=+180 | | 660=6n | | y7,8;y=8 | | 10=t/4-2 | | 8(x=2)=-40 | | 7x=-170 | | 3x+6(x-5=48 | | 10xx=80 | | x+8+8x+1=180 | | u/9=13/11 | | 5-(2x-2)-2x-4=10 | | 3-2n=4n+7 | | 7c=504 | | 8+b/3=11 | | x+x+-7x+-7x=X+9+x-7+2x | | 3^n=51 | | 676=x2 | | 9=t+4–9t | | -7x+41=36-6x | | d/5=27 | | 3x-7+9+-2x=x+2 | | 13=e+5 | | 4.75x=2.50x-54 |

Equations solver categories